PHYTOCENOTIC CHARACTERISTICS OF THE SARSAZAN PASTURE TYPE (HALOCNEMUM STROBILACEUM) OF THE KARAKALPAK USTYRT - Tamambetova, Shakhigul Bayratdinovna (SCIENCE and SOCIETY, 2026)
The article presents the phytocenotic characteristics of the Halocnemum strobilaceum pasture variety (PV), which is part of the Halocnemum strobilaceum pasture type. The described type of pasture is widespread in the central part of the Karakalpak Ustyurt. Halocnemum strobilaceum pasture variety (PV), on wet salt marshes in combination with blinders devoid of vegetation is located in the Kungrad district, geographical points: Shore Barsakelmes, Sarykamysh basin, the area of the pasture variety (PV) is 31495 ha. The total projective cover of the PV is 20%. In the composition of this pasture variety, only 4 species were noted: Halocnemum strobilaceum (Pall.) M. Bieb., Tamarix hispida, Kalidium caspicum (L.) Ung. -Sternb. and Limonium suffruticosum (L.) Kuntze.
Keywords: formation; massif; Halocnemum strobilaceum; Kalidium caspicum; Anabasis salsa; Atraphaxis spinose; Ustyurt Plateau; pastures; landscape; complex